Análise das condições proporcionadas pelos parques tecnológicos para a competitividade das empresas instaladas : o caso das empresas de TI localizadas no TECNOPUC - Neff, Henrique Bagattini (2012)
For being recognized as an exceptional local for companies to settle, technology parks attract the attention of universities or research institutes, government and private enterprise. However, it is not known, for sure, if they actually provide benefits to its tenants. This proposal aims to contribute to this theme, which seeks to identify the contributions offered by the Technology Park of PUCRS - TECNOPUC - and how it influence the competitive factors of firms, in this case IT sector industry installed. Achieving this, using as basis the existing literature on the subject and developed a framework for analyzing the competitive factors of the target company analysis. The research is labeled as exploratory in two phases. The first consists of seven interviews, semi-structured, with managers of IT companies in the Park. The second part consists of the questionnaires, which were made based on the findings of the interviews, also answered by managers of companies, through a link sent by email, with the aim of strengthening the results obtained initially. Eleven questionnaires were answered and, through them, stepped up the research results as a whole. Considering that one of the main goals of technology parks, in theory, is the collaboration between academia, business and government with the creation of an environment of cooperation and the formation of networks between these actors, these characteristics were not identified, as a strong relationship, in TECNOPUC. These results provide an overview of how the TECNOPUC favors the competitiveness of businesses located there, pointing out how this favoritism occurs. From the perspective of managers of IT companies, the Park encourages companies, mainly through the benefits identified as: human resources, infrastructure, status for being installed in the park, location and logistics and innovation environment with new business opportunities. Through these results, new strategies can be adopted, seeking to meet the main objectives of the proposed Park. The instrument developed in this research can be used in other technology parks, to find out what the conditions provided.